Tawhid Uluhiyyah (Oneness of Worship) and Veneration of Saints Tradition - Muchammad Ikfil Chasan; Arif Zamhari (JURNAL INDO-ISLAMIKA, 2021)
This study examines the arguments of saints veneration according to Ayatollah Ja’far al-Subhani’s as one of the Shia Muslim scholars. This is qualitative study using literary research methods to obtain and analyze data with descriptive analysis techniques. Its primary source is the book buhuth qur’aniyyah fi al-tawhid wa al-shirk written by Ja’far al-Subhani himself. On the one hand, some Muslim scholars argue that the veneration of saints tradition including tabarruk (seeking blessings), tawassul (mediation), and tashaffu’ (seeking help) is an act of shirk as it suggests to worship other than Allah, and therefore violates the principle of tawhid uluhiyyah (oneness of worship) stating that Muslims must only worship Allah. On the other hand, Al-Subhani sees the tradition differently. Referring to his definition of worship (‘ibadah), he says that the veneration of saints does not violate the concept of tawhid uluhiyyah, but it is in line with tawhid. He sees it as an act of taqarrub (seeking proximity) which leads a Muslim to get closer to Allah, considering the saints are basically people having a special relationship with Allah.